Manuka honey, a unique mono-floral honey. A comprehensive review of its bioactives, metabolism, action mechanisms, and therapeutic merits. (August 2021) - El-Senduny, Fardous F.; Hegazi, Nesrine M.; Abd Elghani, Ghada E.; Farag, Mohamed A.
Abstract: Manuka honey (MH) is a mono-floral honey obtained from the Manuka tree ( Leptospermum scoparium ) belonging to the Myrtaceae family and grows as a shrub or a small tree mostly throughout New Zealand and Eastern Australia. MH is highly valued for its non-peroxide antibacterial properties mainly attributed to its exclusive content of methylglyoxal (MGO). Additionally, MH is rich in macro-and micro-nutrients including, sugars, free amino acids, proteins, enzymes, essential minerals, vitamins, and various secondary metabolites (flavonoids, phenolic acids, and 1, 2-dicarbonyl compounds). The presence of these beneficial phytochemicals is directly linked to its favored health benefits viz., wound healing, anticancer, antioxidant, and anti-inflammatory effects. Significant modern pharmacological and clinical evidence have highlighted the wide medicinal applications of MH as a unique mono-floral honey. This comprehensive review capitalizes on MH with emphasis on the interrelationship between its holistic chemical composition, metabolism, action mechanisms, and health effects. Moreover, the review recapitulates the diverse health benefits of MH and related patents in food and functional food applications. MH health benefits are credited to its unique chemical composition. It represents an alternative remedy for different ailments to include bacterial, fungal, parasitic, and viral infections, and is currently exploited in a massive number of patents. Nevertheless, further studies are needed to uncover its action mechanism in wound healing, how to improve its pharmacokinetics, and to identify its bio-transformed metabolites inside the body.